2020
DOI: 10.3389/fped.2020.00511
|View full text |Cite
|
Sign up to set email alerts
|

Potential Effect of COVID-19 on Maternal and Infant Outcome: Lesson From SARS

Abstract: The coronavirus disease 2019 (COVID-19), caused by SARS-CoV-2, is highly infectious and its ongoing outbreak has been declared a global pandemic by the WHO. Pregnant women are susceptible to respiratory pathogens and the development of severe pneumonia, suggesting the urgent need to assess the potential maternal and infant outcome of pregnancy with COVID-19. The intrauterine vertical transmission potential of SARS-CoV-2 also remains controversial. Herein, we discuss the potential effect of COVID-19 on maternal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 78 publications
(171 reference statements)
1
5
0
Order By: Relevance
“…5 This was also similar to the study of Wang et al where universal SARS-CoV-2 screening for women admitted for delivery found that all women with positive test results were asymptomatic at the time of testing. 9 The same study also noted that the clinical characteristics of COVID-19 infection in pregnancy were similar to those reported for non-pregnant adults with COVID-19 infection. In brief, Wang et al reported the typical symptoms in positive pregnant women, includes fever, cough, myalgia, malaise and sore throat, and none of them developed severe COVID-19 pneumonia or died.…”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations
“…5 This was also similar to the study of Wang et al where universal SARS-CoV-2 screening for women admitted for delivery found that all women with positive test results were asymptomatic at the time of testing. 9 The same study also noted that the clinical characteristics of COVID-19 infection in pregnancy were similar to those reported for non-pregnant adults with COVID-19 infection. In brief, Wang et al reported the typical symptoms in positive pregnant women, includes fever, cough, myalgia, malaise and sore throat, and none of them developed severe COVID-19 pneumonia or died.…”
Section: Discussionsupporting
confidence: 63%
“…Wang et al also reported that there was no positive RT-PCR result in neonate specimens obtained within 24 hours post-birth, implying no virologic evidence for congenital infection. 9 However, the serologic characteristics of infants reported showed 3 neonates with elevated IgM antibodies to SARS-CoV-2 born to mothers with COVID-19, suggesting a possible vertical transmission of SARS-CoV-2 from mother to newborn. They suggested that this inconsistency may be due to the disruption of the placenta or amniotic barrier caused by the inflammatory mediators from mothers that, induced by SARS-CoV-2, facilitates the transfer of IgG and IgM.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Although COVID-19 has been linked to a high risk of maternal mortality and severe maternal illness (Akhtar et al, 2020) its effect on the development and outcome of infants should be taken into account. For instance, during the SARS-CoV outbreak, maternal pneumonia was related with a high incidence of adverse pregnancy outcomes (Wang, Wang et al, 2020). In the current study, the results were similar to earlier studies and no severe neonatal adverse outcomes of COVID-19 was found (Zheng, et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Concerns arose regarding its impact on vulnerable populations, such as pregnant women, maternal–fetal effects, and long-term consequences [ 2 , 3 ]. Despite evidence that vertical transmission of SARS-CoV-2 is unlikely, it is essential to establish potential maternal–fetal short- and long-term consequences of SARS-CoV-2 infection, especially the potential neuro-cognitive and psychologic outcome of the offspring [ 4 , 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%